Serviço social e violência sexual: reflexões a partir do trabalho da Rede de Atenção à Violência Sexual de Diadema - Siqueira, Andreia Conceição (2010)
The objective of this paper is reflecting on the social worker professional deed action front to sexual violence situations, and as an object, RAVIS (a sexual violence attention chain) from Diadema municipality. Methodologically, we chose to do semistructured interviews with professionals from the Social Service who works at public and private institutions in that city and chain. Either we try to study the validity of the chain work proposal as one of the instruments of social workers intervention face to the sexual violence situations and publish RAVIS experience in this field. We organized the paper in four chapters. The first one sorts the concept of violence and sexual violence out. The second deals with the aspects of the social service history and the violence presence in this process. On the third chapter we did a Diadema municipality record. We conceptualized the chain work and we presented RAVIS record, and finally, we presented the research methodology way, besides, we showed the analysis of the done interviews with which we could realize the chain work has qualified the social worker professional deed and that has exerted an articulator and organizer function to the deeds from several professional areas and groups who works with fighting against the sexual violence in Diadema. The chain work seems us essential for the confrontation of that violence expression that is extremely dense and multifaceted, what doesn t eliminate the necessity of expansion and qualification from the actions that being carried out by RAVIS and for whom the social service has great contribution to be made